IMF Committee on Balance of Payments Statistics : Annual Report 2019 - Sanchez-Munoz, Carlos; Austin, Paul.; Hierro, Alicia; Razin, Tamara (Washington, D.C. : International Monetary Fund, 2020)
The 2019 Annual Report of the IMF Committee on Balance of Payments Statistics (the Committee) provides an overview of recent trends in global balance of payments and international investment position statistics, summarizes the Committee's work during 2019, and presents the work program of the Committee in the coming year.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet